Realizing a Digital School Ecosystem through the Use of Classpoint at SMP Negeri 7 Medan - Budi Valianto; Abdurahman Adisaputera; Ahmad Albar Tanjung; Eva Nirmala Sari Chaniago (GUYUB: Journal of Community Engagement, 2025)
Digital transformation in education has become essential to creating an adaptive and innovative digital school ecosystem. However, SMP Negeri 7 Medan still faces challenges related to teachers’ limited competence in utilizing interactive learning media. This Community Service Program aims to provide solutions through mentoring on the use of Classpoint as an interactive learning tool. The method employed is Participatory Action Research (PAR), engaging 20 teachers in problem identification, planning, training, reflection, and follow-up activities. The implementation strategies included lectures, discussions, and hands-on practice.The evaluation results indicate a significant improvement in teachers’ competence. The average knowledge score increased by more than 50% from pre-test to post-test; 80% of participants mastered basic to advanced Classpoint features, and 70% directly applied them in classroom teaching. Participant satisfaction reached 85%. The program also had a tangible impact on teaching practices, shifting from conventional lecture-based methods toward more interactive and participatory learning. Teachers began integrating quizzes, polls, and digital activities that enhanced student engagement and collaboration. Thus, the program not only improved teachers’ digital skills but also marked an initial step toward building a digital school ecosystem at SMP Negeri 7 Medan.